Torts and other wrongs - Gardner, John 1965-2019 (Oxford University Press, 2019)
Torts and other wrongs is a collection of eleven of the author's essays on the theory of the law of torts and its place in the law more generally. Two new essays accompany nine previously published pieces, a number of which are already established classics of theoretical writing on private law. Together they range across the distinction between torts and other wrongs, the moral significance of outcomes, the nature and role of corrective and distributive justice, the justification of strict liability, the nature of the reasonable person standard, and the role of public policy in tort adjudication. Though focussed on the law of torts, the wide-ranging analysis in each chapter will speak to theorists of private law more generally.